An experiment-based methodology to understand the dynamics of group decision making. (December 2016) - Mason, Susan G.; Holley, Don; Wells, Aaron; Jain, Amit; Wuerzer, Thomas; Joshi, Alark
Highlights: An experiment based methodology is proposed for understanding group decision making. We find SNA tools are more appropriate than traditional statistical methods for understanding group dynamics. Crucial decision points are a key component of group decision making. Understanding the dynamics of group decisions has great potential for creating a transformation in a networked society.